Efficacy and safety of R-GemOx regimen for relapsed refractory B-cell lymphoma: a single-arm Meta analysis - Guo-Xin HUANG; Qi-Long CAO; Jian-Zhou TIAN; Jin-Wei AI; Gao-Jing QU; Bin PEI (Yixue xinzhi zazhi)
Objective Systematic evaluation of the efficacy and safety of the Rituximab plus gemcitabine and oxaliplatin(R-GemOx) regimen for the treatment of relapsed refractory B-cell lymphoma.Methods The PubMed, Embase, CNKI, CBM, VIP and Wan-Fang databases were systematically searched for experimental and observational studies on the R-GemOx regimen for relapsed refractory B-cell lymphoma. The search time frame is from the establishment of each database to September 13, 2022. After extracting the literature and evaluating the quality of the literature in parallel, Meta-analysis was performed using R(4.2.1) software.Results A total of 526 cases of relapsed refractory B-cell lymphoma were included in 13 studies. Meta-analysis showed that the complete response rate(CRR) was 37.48% [95%CI(30.25%, 46.45%)] ; partial response rate(PRR) was 28.62% [95%CI(21.06%, 38.90%)]; stable disease rate(SDR) was 12.03% [95%CI(7.03%, 17.93%)] ; progressive disease rate(PDR) was 21.20% [95%CI(15.73%, 27.22%)]; over response rate(ORR) was 62.19% [95%CI(52.25%, 74.02%)] ; clinical benefit rate(CBR) was 79.40% [95%CI(72.49%, 85.62%)]. Safety was dominated by hematological system toxicity, digestive system toxicity and nervous system toxicity.Conclusion The R-GemOx regimen for relapsed refractory B-cell lymphoma is an effective treatment option with tolerable drug toxicity.